Return to the dreaming - Yurrawalla; Holmes, Cecil, 1921-1994 (Australian Ark documentary series., 1986)
This is the story of the return, after 40 years, of an Australian aborigine to his tribal home. The nearly blind aborigine, Yurrawalla, is less westernized than younger members of his tribe, so he remains in touch with the extraordinary world of the "dreaming time" and thus he can face the spirits of his ancestors and pass on their secrets to his children. His paintings on rock and bark conjure a mystical world of spiritual beings and fantastic beasts.